Ontario Neurodegenerative Disease Research Initiative (ONDRI): Structural MRI Methods and Outcome Measures - Ramirez, Joel; Holmes, Melissa F.; Scott, Christopher J. M.; Ozzoude, Miracle; Adamo, Sabrina; Szilagyi, Gregory M.; Goubran, Maged; Gao, Fuqiang; Arnott, Stephen R.; Lawrence-Dewar, Jane M.; Beaton, Derek; Strother, Stephen C.; et al. (Frontiers in Neurology, 2020)
The Ontario Neurodegenerative Research Initiative (ONDRI) is a 3 year multi-site prospective cohort study that has acquired comprehensive multiple assessment platform data, including 3T structural MRI, from neurodegenerative patients with Alzheimer’s disease, mild cognitive impairment, Parkinson’s disease, amyotrophic lateral sclerosis, frontotemporal dementia, and cerebrovascular disease. This heterogeneous cross-section of patients with complex neurodegenerative and neurovascular pathologies pose significant challenges for standard neuroimaging tools. To effectively quantify regional measures of normal and pathological brain tissue volumes, the ONDRI neuroimaging platform implemented a semi-automated MRI processing pipeline that was able to address many of the challenges resulting from this heterogeneity. This purpose of this paper is to serve as a reference and conceptual overview of the comprehensive neuroimaging pipeline used to generate regional brain tissue volumes & neurovascular marker data that will be made publicly available online.